2022
DOI: 10.3390/biomedicines10061253
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LOC101927355 as a Novel Biomarker for Preeclampsia

Abstract: Preeclampsia, a disorder with a heterogeneous physiopathology, can be attributed to maternal, fetal, and/or placental factors. Long non-coding RNAs (lncRNAs) refer to a class of non-coding RNAs, the essential regulators of biological processes; their differential expression has been associated with the pathogenesis of multiple diseases. The study aimed to identify lncRNAs, expressed in the placentas and plasma of patients who presented with preeclampsia, as potential putative biomarkers of the disease. In sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Among the paradigmatic genes modified connected to placental disorders, we can mention the long non-coding RNA UCA1 , upregulated more than 4-fold by the T188N mutant compared to the WT STOX1A. UCA1 is induced in the preeclamptic placenta 23 and was shown to be connected to trophoblast cell migration, 19 cell invasion and proliferation, 18 trophoblast fusion, 17 and the ability to trigger endothelial injuries through UCA1-loaded trophoblast exosomes. 24 In the genes specifically induced by the R364X mutant, it is noticeable that the metallothionein gene cluster is upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Among the paradigmatic genes modified connected to placental disorders, we can mention the long non-coding RNA UCA1 , upregulated more than 4-fold by the T188N mutant compared to the WT STOX1A. UCA1 is induced in the preeclamptic placenta 23 and was shown to be connected to trophoblast cell migration, 19 cell invasion and proliferation, 18 trophoblast fusion, 17 and the ability to trigger endothelial injuries through UCA1-loaded trophoblast exosomes. 24 In the genes specifically induced by the R364X mutant, it is noticeable that the metallothionein gene cluster is upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…NRAD1, also known as LINC00284, was localized to the nucleus and bound chromatin to affect gene expression (41). A recent study (42) demonstrated that NRAD1 was significantly downregulated in PE placental samples. Lysophosphatidic acid (LPA) exerted a variety of biological effects, including motility and proliferation, by binding to the LPA receptor LPAR1-6.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are currently no studies that have identified lncRNAs as first trimester diagnostic biomarkers to support the early diagnosis of placental disorders. Peñailillo et al [ 155 ] recently attempted to address this gap in the literature. Their study showed that lncRNA LOC101927355 is decreased in the placenta and maternal plasma at the time of delivery in patients with PE, for which it could represent a new potential biomarker.…”
Section: Non-protein Placental Biomarkersmentioning
confidence: 99%